2020
DOI: 10.3390/polym12112443
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Polyacrylic Acid-Grafted PVDF Nanofiltration Membrane with Good Antifouling Property for the Textile Industry

Abstract: In the textile industry, a high-efficiency dye removal and low-retention of salt is demanded for recycling wastewater. In this study, polyvinylidene fluoride (PVDF) ultrafiltration membrane was transformed to a negatively charged loose nanofiltration (NF) membrane through UV-grafting of acrylic acid. At the optimal exposure of PVDF membrane in UV light for 5 min, the membrane had a high dye recovery above 99% (Congo red and Eriochrome® Black T) and a low sodium chloride (NaCl) rejection of less than 15% along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 45 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…The optimal membrane sample shows permeability of 2600 Lm −2 h −1 bar −1 for oil/water emulsion filtration with >98% of oil rejection. Recently, Chiao et al [ 18 ] transformed PVDF ultrafiltration membrane to a negatively charged loose nanofiltration membrane through UV-grafting of acrylic acid for dye removal from textile wastewater. It was found that the optimal exposure time of PVDF membrane to UV light is 5 min.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal membrane sample shows permeability of 2600 Lm −2 h −1 bar −1 for oil/water emulsion filtration with >98% of oil rejection. Recently, Chiao et al [ 18 ] transformed PVDF ultrafiltration membrane to a negatively charged loose nanofiltration membrane through UV-grafting of acrylic acid for dye removal from textile wastewater. It was found that the optimal exposure time of PVDF membrane to UV light is 5 min.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, biofouling is one of the most challenging issues in the application of material in natural water-based environments. Several strategies are applied to prevent biofouling [ 45 , 46 , 47 , 48 ]; application of suitable hydrogel is one of them. Thus, it is noteworthy that both hydrogel components as polyacrylic [ 49 ] as well as zwitterionic-based materials [ 50 , 51 ] are well known for their antibiofouling properties and underwater stability [ 52 ], making them attractive as a robust alternative and exhibiting promising potential, in terms of energy recovery, for blue energy harvesting near seawater–fresh water borders and as a water-salinity-driven actuator in underwater engineering and robotics by adopting appropriate hydrogels with polyelectrolyte and antipolyelectrolyte effects.…”
Section: Discussionmentioning
confidence: 99%
“…The feed solution and the permeated water have particular electrical conductivity values. C f and C p are the electrical conductivity of the feed solution and the permeated water, respectively 8 . …”
Section: Reagents and Experimentalmentioning
confidence: 99%
“…Lately, NF membrane has attracted much attention for employment in a specific water purification technology, such as wastewater treatment, distillation, pollutants adsorption, and bio-products recovery. Therefore, most researchers attempt to utilize NF membrane owing to outstanding advantages, including the practical rejection of ions or low molecular weight organic materials (approximately ranging from 200 to 1000 g/mol), the spectacular of the PWF, the lower hydraulic pressure than Reverse Osmosis, and the inexpensive process by energy-saving strategies 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%